Study on the effect of Esketamine in children undergoing strabismus correction surgery - DING Yichao; SUN Zuojun; QU Jingyu; ZHANG Jing; HAN Banggui; ZENG Yongheng (Yixue xinzhi zazhi)
Objective To investigate the effect of Esketamine in children undergoing strabismus correction surgery. Methods Children who were scheduled to undergo strabismus surgery were divided into the Esketamine group (ES group) and Fentanyl group (control group). Esketamine 0.5 mg/kg was injected intravenously for anesthesia induction in the ES group, and Fentanyl 2 μg/ kg was administered intravenously for anesthesia induction in the control group. Remifentanil 0.1~0.3 μg/kg/min was injected intravenously to maintain anesthesia in both groups. The diastolic blood pressure, systolic blood pressure and heart rate of all children before induction, 60 seconds after induction, and after the operation were observed and recorded in all children. Children's FLACC analgesia scores and occurrence of adverse events (nausea and vomiting, hallucinations, excessive sedation, agitation), eye position one week after surgery and one month after surgery during recovery from anaesthesia were also recorded. Results A total of 86 pediatric patients were included, with 43 in the ES group and 43 in the control group. At the three time points, there was no significant difference in diastolic and systolic blood pressure between the two groups (P>0.05), but heart rate in the ES group was significantly higher than the contorl group (P<0.05). The FLACC score of the ES group was higher than that of the control group (P<0.05). There was no difference in the incidence of adverse events between two groups (P>0.05). The orthotopic rates at 1 week and 1 month after surgery had no significant differences between two groups (P>0.05). Conclusion In pediatric strabismus surgery, Esketamine has a better analgesic effect than Fentanyl, and does not significantly increase side effects or affect postoperative eye position.